Framing Russia-Ukraine war and Vladimir Putin’s image: a content analysis of New York Times online commentary articles - Lim, Lai Hoon (Penerbit Universiti Kebangsaan Malaysia, 2023)
The news of Russia launching a full-scale invasion of Ukraine on 24 February 2022 shocked the world. However, the media has different interpretations of this invasion. Ukrainian and Western media use the term “war,” whereas the Russian media call it a “special military operation”. Storylines or frames provided by mass media greatly influence public perception of the situation. Once a frame has become extensive in media discourse, it raises the public’s expectation of the political legitimation actions by discussing the possible consequences of the crisis. From that perspective, this study examines the framing of the Russia-Ukraine war and Russian President Vladimir Putin’s image in one renowned America-based media, The New York Times Online. A qualitative content analysis of commentary articles under the “Opinion” column was performed. Two hundred twenty-nine commentary articles were content analysed from 24 February 2022 to 24 December 2022. The qualitative content analysis enables the study to scrutinise the framed content of the war and the constructive and destructive character of Putin’s image portrayal. Agenda setting and framing theory were used as the theoretical framework. The analysis inductively generates thematic frames by systemising the content of the articles. The findings reveal that Russia was framed as an unprovoked invader who has unmercifully onslaught Ukraine while Ukraine strives to put up an inspiring defence of its sovereignty. The image of Vladimir Putin carries a destructive character where the portrayal is conspiratorial and seclusive.